Disruptions to routine childhood vaccinations in low- and middle-income countries during the COVID-19 pandemic: A systematic review - Alexandra M. Cardoso Pinto; Lasith Ranasinghe; Peter J. Dodd; Shyam Sundar Budhathoki; James A. Seddon; James A. Seddon; Elizabeth Whittaker (Frontiers Media S.A., 2022)
BackgroundThe COVID-19 pandemic has disrupted routine childhood vaccinations worldwide with low- and middle-income countries (LMICs) most affected. This study aims to quantify levels of disruption to routine vaccinations in LMICs.MethodsA systematic review (PROSPERO CRD42021286386) was conducted of MEDLINE, Embase, Global Health, CINAHL, Scopus and MedRxiv, on the 11th of February 2022. Primary research studies published from January 2020 onwards were included if they reported levels of routine pediatrics vaccinations before and after March 2020. Study appraisal was performed using NHLBI tool for cross-sectional studies. Levels of disruption were summarized using medians and interquartile ranges.ResultsA total of 39 cross-sectional studies were identified. These showed an overall relative median decline of −10.8% [interquartile range (IQR) −27.6%, −1.4%] across all vaccines. Upper-middle-income countries (upper-MICs) (−14.3%; IQR −24.3%, −2.4%) and lower-MICs (−18.0%; IQR −48.6%, −4.1%) showed greater declines than low-income countries (−3.1%; IQR −12.8%, 2.9%), as did vaccines administered at birth (−11.8%; IQR −27.7%, −3.5%) compared to those given after birth (−8.0%; IQR −28.6%, −0.4%). Declines during the first 3 months of the pandemic (−8.1%; IQR −35.1%, −1.4%) were greater than during the remainder of 2020 (−3.9%; IQR −13.0%, 11.4%) compared to baseline.ConclusionThere has been a decline in routine pediatric vaccination, greatest in MICs and for vaccines administered at birth. Nations must prioritize catch-up programs alongside public health messaging to encourage vaccine uptake.Systematic review registrationIdentifier: CRD42021286386.